The trends in anesthesiology research in Colombia: A brief bibliometric analysis.: Tendencias en investigación en Anestesiología en Colombia: Un breve análisis bibliométrico - Bermúdez–Moyano , Stefanya Geraldine (2024)
Monitoring trends in clinical and biomedical research in anesthesiology is essential due to its interconnection with various medical specialties, such as cardiology, neurology and surgery.